ANALISIS KETERBUKAAN INFORMASI TERHADAP KEPERCAYAAN PUBLIK: PERSPEKTIF PUBLIC RELATIONS PADA PT PLN ICON PLUS SUMATERA BAGIAN SELATAN - Muhammad Alfani (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2025)
Public transparency is a fundamental issue in building public trust in institutions or organizations. This study aims to identify and analyze the impact of information transparency at PT PLN Icon Plus on public trust in the company, as well as to disseminate information on the influence of transparency on the level of trust. The research method applied in this study is a descriptive method with a qualitative approach to reveal or investigate information in more detail. The analysis was carried out by describing public trust in PT PLN Icon Plus in South Sumatra through interviews with a number of sources. The data collection methods applied include field observations, in-depth interviews with information sources, and the roles and involvements that have been recorded by the author as primary data, and documentation and literature studies as secondary data. The research findings show that public information transparency at PT PLN Icon Plus South Sumatra has functioned optimally and meets the criteria for transparency. Transparency can be explained through four dimensions: leadership commitment, formal processes, training programs, and communication with stakeholders. The challenge faced is that complex technical and operational information is difficult to achieve without sacrificing accuracy, which can cause confusion among the public.